The legitimacy of the process of rehabilitation of the perpetrators of homicides - Joanna Waszczuk; Magdalena Trzeciak (Rozprawy Społeczne)
Abstract The article concerns the legitimacy of the perpetrators of homicides in the opinion of people aged 18-30 and over 60.